Against massacre : humanitarian interventions in the Ottoman Empire, 1815-1914 : the emergence of a European concept and international practice - Rodogno, Davide, 1972- (Human rights and crimes against humanity., 2012)
"Against Massacre looks at the rise of humanitarian intervention in the nineteenth century, from the fall of Napoleon to the First World War. Examining the concept from a historical perspective, Davide Rodogno explores the understudied cases of European interventions and noninterventions in the Ottoman Empire and brings a new view to this international practice for the contemporary era. While it is commonly believed that humanitarian interventions are a fairly recent development, Rodogno demonstrates that almost two centuries ago an international community, under the aegis of certain European powers, claimed a moral and political right to intervene in other states' affairs to save strangers from massacre, atrocity, or extermination. On some occasions, these powers acted to protect fellow Christians when allegedly "uncivilized" states, like the Ottoman Empire, violated a "right to life." Exploring the political, legal, and moral status, as well as European perceptions, of the Ottoman Empire, Rodogno investigates the reasons that were put forward to exclude the Ottomans from the so-called Family of Nations. He considers the claims and mixed motives of intervening states for aiding humanity, the relationship between public outcry and state action or inaction, and the bias and selectiveness of governments and campaigners. An original account of humanitarian interventions some two centuries ago, Against Massacre investigates the varied consequences of European involvement in the Ottoman Empire and the lessons that can be learned for similar actions today"--Provided by publisher.